Exploring Speaking Anxiety Among Eleventh-Grade EFL Students at Sma Tahfiz Al-Batthawi NWDI Kerongkong - Adawiyah, Siti Robiatul; Usuluddin, Usuluddin; Maysuroh, Siti; Agustina, Yulia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the factors contributing to students’ speaking anxiety and the types of anxiety experienced by Grade 11 students at SMA Tahfiz Al-Batthawi NWDI Kerongkong in the 2025/2026 academic year. Using a qualitative descriptive approach, data were collected through observations, interviews, and questionnaires from six students. The findings reveal four main factors causing speaking anxiety: limited vocabulary, difficulties in pronunciation, fear of making mistakes, and fear of negative evaluation. The study also identifies three types of anxiety: state anxiety, trait anxiety, and situation-specific anxiety. These findings highlight that speaking anxiety significantly hinders students’ confidence and performance in English learning. The results suggest that teachers should create supportive classroom environments and provide strategies to reduce anxiety, thereby encouraging students to participate more actively in speaking activities.